2008
DOI: 10.2174/157340608784325098
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin Conjugates with Glucose Moieties Designed as Drug Carriers: Their Syntheses, Evaluations Using Concanavalin A and Doxorubicin, and Structural Analyses by NMR Spectroscopy

Abstract: Three kinds of beta-cyclodextrin derivatives conjugated with glucose moieties, which were expected as models for a drug carrier targeting the drug delivery systems, were designed and synthesized from beta-cyclodextrin and the natural product, 4-hydroxyphenyl-beta-D-glucopyranoside called arbutin. Arbutin was used because it had a phenyl group with a hydroxyl function which could be used to link the glucose moiety to beta-cyclodextrin. The evaluations of these conjugates as the drug-carrying molecules were done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In these compounds, the distance between the two anchored glycotopes can be modulated by varying the spacer link connecting the external sugars and the CD core (Scheme 7). [68][69][70][71] This feature was exploited by the authors to estimate the separation between two bGal binding sites in peanut agglutinin (PNA) lectin by employing surface plasmon resonance (SPR). They also confirmed that the inclusion properties of bCD remained operative in the bis-conjugates, using doxorubicin as a model guest.…”
Section: Regioselectively Substituted CD Bis-glycoconjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In these compounds, the distance between the two anchored glycotopes can be modulated by varying the spacer link connecting the external sugars and the CD core (Scheme 7). [68][69][70][71] This feature was exploited by the authors to estimate the separation between two bGal binding sites in peanut agglutinin (PNA) lectin by employing surface plasmon resonance (SPR). They also confirmed that the inclusion properties of bCD remained operative in the bis-conjugates, using doxorubicin as a model guest.…”
Section: Regioselectively Substituted CD Bis-glycoconjugatesmentioning
confidence: 99%
“…118 The multivalent supramolecules are comprised of a fluorescent ruthenium(II) core functionalized with 2, 4 or 6 adamantyl units (71) that act as anchor elements for bCD conjugates. Heptavalent glycoclusters in which the bCD platform was homogeneously substituted at the primary C-6 positions with 2-(a-D-mannopyranosyloxy)ethylthio branches (72) were self-assembled onto this core to form complexes exposing 14, 28 or 42 mannopyranosyl units (73) with a unique spatial orientation (Scheme 31).…”
Section: Supramolecular Glycoclustersmentioning
confidence: 99%
“…11,12) Moreover, drug targeting can also be achieved by using drug vehicles sensitive to the surrounding enzymes, temperature or pH. [13][14][15] Recently, several studies reported [16][17][18][19][20][21][22][23] that introduction of a suitable substituent (e.g., glucose, galactose, arbutin, hydroquinone α-glycoside, porphyrin, or β-carboline) to the rim of α-and β-CDs, can enhance the binding affinity towards DOX through cooperative interactions between the CD's cavity and guest molecules. Although, α-and β-CD are the most exploited CDs, 24) little has been published on γ-CD (1) as targeted drug delivery system.…”
Section: 4)mentioning
confidence: 99%
“…Diffusion-ordered NMR spectroscopy (DOSY), which displays the PGSE NMR data in a two-dimensional spectrum, is a practical experiment for separating the 1 H NMR spectra of different species [2]. In addition to the DOSY separation of a mixture, the DOSY method has been widely used for the characterization of high-molecular-weight polymeric compounds and the identification of supramolecular structures [3][4][5][6][7][8]. However, the DOSY method has generally failed to identify the isomeric species of similar size and structure because of their similar diffusion coefficients.…”
Section: Introductionmentioning
confidence: 99%